Evaluation of the Efficacy of Selected Fungicides for Powdery Mildew Control in Carrot Seed Plants in Central Oregon, 2025 - Jeremiah K. S. Dung (Plant Health Progress, 2026)
Powdery mildew, caused by the fungus Erysiphe heraclei, is a common disease of carrot grown for seed in the United States. Symptoms include white, powdery fungal growth on foliage, stems, and umbels that can lead to chlorosis and premature senescence. This report evaluates the efficacy of various fungicides for the management of powdery mildew on carrot leaves. The trial was conducted in 2025 in Madras, OR, on a proprietary inbred parent line of a hybrid carrot cultivar. Significant differences in fungicide efficacy were observed, and these results can help growers develop more effective management programs for this disease.